2009
DOI: 10.1016/j.ceb.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Rautenlippe Redux—toward a unified view of the precerebellar rhombic lip

Abstract: The rhombic lip (aka rautenlippe) is a germinative neuroepithelium rimming the opening of the hindbrain fourth ventricle during development. Studies spanning more than a century have shown that the rhombic lip produces numerous brainstem neuronal populations unique in their development and functions. While these studies have largely been anatomical in nature, recent applications of newer techniques such as genetic fate mapping and conditional mutagenesis have resolved the rhombic lip into numerous molecularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…H&E-stained sections displayed typical histology with intratumoral nodules (e), and Gomori silver staining confirmed internodular desmoplasia (f). Global gene expression profile from this tumor displayed constitutive Sonic hedgehog signaling (g) types of the cerebellum, the lower rhombic lip (LRL), divided into the auditory and precerebellar compartment, produces cells that form parts of the cochlear nucleus complex and the precerebellar system, respectively [5,14,17,26]. So far, two different progenitor cell populations within the rhombic lip have been identified as possible origins for MB.…”
Section: Discussionmentioning
confidence: 99%
“…H&E-stained sections displayed typical histology with intratumoral nodules (e), and Gomori silver staining confirmed internodular desmoplasia (f). Global gene expression profile from this tumor displayed constitutive Sonic hedgehog signaling (g) types of the cerebellum, the lower rhombic lip (LRL), divided into the auditory and precerebellar compartment, produces cells that form parts of the cochlear nucleus complex and the precerebellar system, respectively [5,14,17,26]. So far, two different progenitor cell populations within the rhombic lip have been identified as possible origins for MB.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, wnt1 is expressed in a decreasing dorsoventral gradient in the LRL, likely extending ventrally beyond the ngn1 domain (Landsberg et al, 2005; Ray and Dymecki, 2009). Using Cre and Flp based fate mapping studies, Rodriguez and Dymecki (2000) and Landsberg et al (2005) showed that mossy fiber-type precerebellar nuclei (BP, RTN, LRN, ECN) derive from the strongly wnt1 and math1 expressing dorsal LRL domain, while the climbing fiber system (IO) derives from weakly wnt1 and strongly ngn1 expressing ventral LRL domain.…”
Section: Molecular Revolutionsmentioning
confidence: 99%
“…Eph receptor-ephrin signaling furthermore partakes in cell segregation and positioning, tissue segmentation, cell migration, axon guidance, topographic mapping and morphogenesis rhombic lip likely contributes to the LL, whereas the complete CNC as well as a subpopulation of excitatory (glutamatergic) neurons of the SOC are descended from the lower rhombic lip of r2 to r5 (Farago et al 2006;Nichols and Bruce 2006;Rose et al 2009). This area of the lower rhombic lip is therefore also termed the auditory lip, whereas the lower rhombic lip from r6 to r8 (possibly until r11) is called the precerebellar lip (Farago et al 2006;Ray and Dymecki 2009) (Fig. 2).…”
Section: Embryonic Origin Of the Auditory Hindbrainmentioning
confidence: 99%